Modelling and animation of 3D objects for 3D holographic display - Yeo, Eng Thai. (2010)
Interest in three dimensional (3D) display technologies greatly increased over the years and the ability to view objects with depth information being a major motivation. There are different ways of achieving such 3D effects, and one such way discussed in this report is holography. Holography is the technique used to record light interference between two beams and later reconstruction using diffraction. However there are still some limitations to holography itself like the need of physical object and recording media to be present for generation of hologram. These limitations reduced the types of object that can be used to generated holograms. Hence, a venture to computer generated hologram was made. It does not require any physical objects or recording media during the generation of hologram as all is done using a computer. And to achieve this, a program is used with aid from a graphic processor unit (GPU) to compute the light intensity on every pixel of the hologram. The purpose of this project is to do research on 3D display technology, mainly holography. And to model 3D objects using Autodesk 3ds Max. An attempt to introduce occlusion was also made using ray tracing technique. The current program used omits occlusion in it computation as it will greatly increase the complexity of the program and its computation time. However without occlusion, the object reconstructed will look as though transparent and less realistic. And from the results, computer generated hologram had shown potential in the generation of holograms. It indeed removed the need for the presence of physical objects and recording media in the generation of hologram and increased the types of object that can be used. Although the implementation of occlusion was unsuccessful, the logic and principle employed are reasonable and feasible. Future work on reviewing the edited codes for occlusion can be made to improve on it.